Digital Libraries Impact on Students' Learning Behaviour. Case Study: Medical Students - Volovici, Rodica; Fratila, Anca; Bera, Liana Gabriela; Moisil, Ioana (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
Advanced web-based technologies and the advent of cloud computing have transformed the academic library into the core provider of digital information and learning resources. The “Lucian Blaga” University of Sibiu has one of the most advanced digital libraries of Romania. In order to enhance the quality of the library services we have designed an exploratory study aimed to asses the impact of the digital library on student learning behaviour. Students, from almost all faculties (medicine and pharmacy, engineering, sciences, history and philology, law etc), have been involved in the study. They have been asked to answer to a questionnaire about how they are using the digital library, what other sources of information they are using, if they are satisfied with the library services, if and how they have obtained the required bibliography. The information obtained from questionnaires was compared with data on students' interaction with the digital library and with their learning outcomes. In our paper we are presenting the results of the study applied to students in medical sciences, pharmacy and nursing.